2022
DOI: 10.3389/fimmu.2022.1049812
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of bile biomarkers and their immunoregulatory role in biliary tract cancers

Abstract: Biliary tract cancers (BTCs), including cholangiocarcinoma and gallbladder carcinoma, originate from the biliary epithelium and have a poor prognosis. Surgery is the only choice for cure in the early stage of disease. However, most patients are diagnosed in the advanced stage and lose the chance for surgery. Early diagnosis could significantly improve the prognosis of patients. Bile has complex components and is in direct contact with biliary tract tumors. Bile components are closely related to the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 133 publications
(151 reference statements)
1
9
0
Order By: Relevance
“…In routine blood test, we found that CCA patients had signi cantly higher serum levels of TBIL, ALT, AST, TBA, CA19-9, and CEA than those of gallstone patients, which is consistent with previous reports [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In routine blood test, we found that CCA patients had signi cantly higher serum levels of TBIL, ALT, AST, TBA, CA19-9, and CEA than those of gallstone patients, which is consistent with previous reports [12].…”
Section: Discussionsupporting
confidence: 92%
“…Yun Cheng Li et al summarized the potential diagnostic value of bile markers in biliary tract tumors. Among them, the AUC of Vascular Endothelial Growth Factor levels was as high as 0.93 [12]. In addition, with the continuous development of omics technology, people have used a large amount of genetics, epigenetics, proteomics, and metabolomics to further better identify CCA features.…”
Section: Discussionmentioning
confidence: 99%
“…Blood is the most broadly used type of liquid biopsy specimen in medical research. In addition to blood, body fluids such as saliva [5], sputum [6], cerebrospinal fluid [7][8][9][10][11], bile [12], urine [13][14][15][16][17][18][19][20][21], stool [22][23][24], seminal fluid [25], and uterine lavage fluid [26] have also been explored in a variety of malignancies (shown in Figure 1). There are many substances that can be used as liquid biopsy targets, including circulating tumor DNA (ctDNA), circulating miRNA, exosomes, and tumor-educated platelets (TEP), in addition to circulating tumor cells (CTCs) and circulating cell-free DNA (cfDNA), which are more widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Cholangiocarcinoma (CCA) consists a group of malignant tumours originating from the bile duct epithelium. [1][2][3] CCA, a type of bile duct cancer, is classified into two main subtypes based on its anatomical location: intrahepatic CCA (iCCA) and extrahepatic CCA (eCCA).…”
Section: Introductionmentioning
confidence: 99%